2018
DOI: 10.1038/s41598-018-22034-0
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness, reproducibility, and durability of tailored mobile coaching on diabetes management in policyholders: A randomized, controlled, open-label study

Abstract: This randomized, controlled, open-label study conducted in Kangbuk Samsung Hospital evaluated the effectiveness, reproducibility, and durability of tailored mobile coaching (TMC) on diabetes management. The participants included 148 Korean adult policyholders with type 2 diabetes divided into the Intervention-Maintenance (I-M) group (n = 74) and Control-Intervention (C-I) group (n = 74). Intervention was the addition of TMC to typical diabetes care. In the 6-month phase 1, the I-M group received TMC, and the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 45 publications
(63 reference statements)
1
24
0
Order By: Relevance
“…Randomized control trials and observational studies have shown that using diabetes apps for self-management significantly improves scores of cumulative (40, 56) or individual self-care components (39, 5759). Blood glucose monitoring (56–59), physical activity (57, 59), general diet (39, 56), specific diet (5759), and foot care (39, 58) behaviours have been reported to be significantly improved by using diabetes apps. This is mainly due to the reason that diabetes app use may indeed be a useful approach to improve diabetes knowledge, self-management skills, and knowledge about complications which may ultimately enhance self-care practices (60).…”
Section: Discussionmentioning
confidence: 99%
“…Randomized control trials and observational studies have shown that using diabetes apps for self-management significantly improves scores of cumulative (40, 56) or individual self-care components (39, 5759). Blood glucose monitoring (56–59), physical activity (57, 59), general diet (39, 56), specific diet (5759), and foot care (39, 58) behaviours have been reported to be significantly improved by using diabetes apps. This is mainly due to the reason that diabetes app use may indeed be a useful approach to improve diabetes knowledge, self-management skills, and knowledge about complications which may ultimately enhance self-care practices (60).…”
Section: Discussionmentioning
confidence: 99%
“…Another is ensuring a high-quality data analysis is conducted. There are many previous studies implying the advantages of PHRs and PGHD with positive conclusions of the use of mPHRs [ 14 - 17 ]. The results of these studies were collected on the basis of clinical trials such as nonblinded, open-label randomized controlled trials (RCTs) and cluster-randomized trial designs.…”
Section: Discussionmentioning
confidence: 99%
“…This program was thereafter progressively rolled out to the general public, and it finally achieved universal coverage in 1989. According to the National Health Insurance Act, the criteria for the method, procedure, scope, and upper limit of health care shall be prescribed by the Ministry of Health and Welfare [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations